Challenges in teaching students to plot equations: Another impact of graphing procedures - Umah, Ulumul; Rahmawati, Ana (Universitas Hamzanwadi, 2024)
Graphs are essential representations in mathematics, but many students only focus on procedural rules when sketching graphs of equations. This study aims to describe the errors and obstacles experienced by students in drawing graphics of equations. The research method uses a qualitative approach by collecting data through tests and interviews. The research results show that students' mistakes in drawing graphs can be caused by dependence on procedural knowledge in plotting points without conceptual understanding. Students who make mistakes do not understand points as multiplicative objects, lack covariational reasoning, need help understanding the concept of complex numbers, and show reflective thinking in completing assignments. This research implies that teachers must consider the students' difficulties and mistakes to avoid becoming didactic learning obstacles. In studying plotting point procedures, students' knowledge must include understanding concepts related to graphs, such as the meaning of points and graph concavity, graph shifts, and the relationship between the discriminant of a quadratic equation and its graph.